The Role of High-Flow Nasal Oxygen Therapy (HFNOT) in Emergency Medicine: Efficacy and Clinical Applications - Cholewiński, Szymon; Ciechański, Marcin; Witkowska, Edyta; Wilk, Klaudia; Wilk, Bernadetta; Stachura, Piotr; Kasprzyk, Aleksandra; Pszczoła, Katarzyna; Jurkiewicz, Katarzyna; Rejman, Piotr (Journal of Education, Health and Sport, 2025)
Introduction: High-Flow Nasal Oxygen Therapy (HFNOT) is an increasingly utilized respiratory support modality in emergency medicine. It offers advantages over conventional oxygen therapy (COT) and non-invasive ventilation (NIV), including enhanced oxygenation, patient comfort, and physiological benefits. Despite growing interest, questions remain regarding its optimal use and effectiveness across different clinical scenarios. Materials and methods: This review synthesizes current literature on the use of HFNOT in emergency departments, prehospital care, and patient transport. It explores underlying physiological mechanisms, device setup parameters, and clinical outcomes compared to conventional oxygen therapy (COT) and non-invasive ventilation (NIV), while also addressing limitations and implementation challenges. Results: HFNOT improves oxygenation, reduces work of breathing, and enhances secretion clearance through mechanisms such as dead space washout and mild positive airway pressure. It is well-tolerated and shows promise in managing acute respiratory failure. However, evidence is limited for certain populations, such as those with blunt chest trauma. HFNOT may delay intubation in some cases and requires proper training for safe implementation. Conclusions: HFNOT is a valuable, less invasive respiratory support strategy in emergency medicine. Its use is expected to expand with accumulating evidence and increased provider experience. Further research is needed to define its role in non-critical care settings and specific high-risk groups.